Do Our Introductory Accounting Textbooks Reflect Current Accounting Practice? - Wells, Paul; Sinclair, R (American Accounting Association (AAA), 2016)
Many researchers have found that accounting education contributes to the narrow and stereotypical perceptions students have of accounting, further supporting claims that the profession may be attracting graduates who lack the required skills and capabilities. This study examines how introductory accounting textbooks might contribute to these perceptions. Given that most of these textbooks are adaptations of American textbooks, these findings will have implications for educators and authors beyond New Zealand. This paper provides a call to authors and publishers of these textbooks to acknowledge the wider contribution that accounting makes to society, and to better reflect the influence of technology on the accounting process as currently practised.
Keywords: Accounting education; Introductory accounting; Accounting textbooks